YouTube Social Media in the Development of Online Da'wah for the Millennial Generation in Makassar City - Mutmainna, Nurunnisa; Masri, Abd. Rasyid; Tikke, Arifuddin; Akil, Muhammad Anshar (PT FORMOSA CENDEKIA GLOBAL, 2024)
One of the most crucial aspects of Islam's overall teachings is da'wah. Through da'wah, people can learn about, live out, and apply the principles of Islam from generation to generation. In the modern era of information globalization and the inevitable progress of technology, da'wah is essentially an endeavor to cultivate a predisposition and interest in calling someone to the teachings of Islam. Nothing can be hidden; everything is available, even things that are banned. If the missionaries don't quickly adjust to these developments, they will become obsolete. It's necessary for missionaries to be adept in social media. Islam is no longer the domain of clerics in this millennium. People can learn Islam in a variety of methods and places at any time. Modernization is a necessary step on the journey through space and time that all people must take. A shift in the dai's method of preaching ought to counterbalance this amazing shift in society. Da'wah shouldn't be conducted in a certain location or with just traditional means (lectures). Da'wah needs to be innovative, forward-thinking, and energetic. Da'wah and Islamic communication are two examples of the many patterns of scientific progress that have arisen from the world's rapid flow of knowledge and technology.